2022
DOI: 10.1111/gcb.16093
|View full text |Cite
|
Sign up to set email alerts
|

pH variability at volcanic CO2 seeps regulates coral calcifying fluid chemistry

Abstract: Coral reefs are iconic ecosystems having immense ecological, economic and cultural value, but globally their carbonate-based skeletal construction is threatened by ocean acidification. Identifying coral species that have specialised mechanisms to maintain high rates of calcification in the face of declining seawater pH is of paramount importance to predicting future species composition, and growth of coral reefs. Here, we studied multiple coral species from two distinct volcanic CO2 seeps in Papua New Guinea t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 70 publications
2
22
0
Order By: Relevance
“…Brown et al (2022) incubated coralPocillopora damicornis from both a flat and a sloping reef, where seawater pH variability differed, in aquaria with stable and variable pH. As in our study, they found higher rates of calcification for corals from a more variable environment, probably because they maintained less intracellular pH acidosis, as previously found for other corals (Comeau et al, 2022;Cornwall et al, 2018;Gibbin & Davy, 2014). Clearly, this compensatory mechanism might have a cost.…”
Section: Coral Potential Resilience To Ocean Acidification: What Do W...supporting
confidence: 86%
See 3 more Smart Citations
“…Brown et al (2022) incubated coralPocillopora damicornis from both a flat and a sloping reef, where seawater pH variability differed, in aquaria with stable and variable pH. As in our study, they found higher rates of calcification for corals from a more variable environment, probably because they maintained less intracellular pH acidosis, as previously found for other corals (Comeau et al, 2022;Cornwall et al, 2018;Gibbin & Davy, 2014). Clearly, this compensatory mechanism might have a cost.…”
Section: Coral Potential Resilience To Ocean Acidification: What Do W...supporting
confidence: 86%
“…By assessing the holobiont physiological responses and the Symbiodiniaceae profiles of three coral species from both Bouraké and a Reference reef to a large range in pH, we found that corals from Bouraké constantly exhibited higher growth rates and had a specific and more consistent ITS2 majority sequence than corals from the Reference reef under low and variable pH conditions. It seems likely that such patterns were linked to the strong life-long environmental fluctuations, which might have promoted coral resilience as previously suggested (e.g., Brown et al, 2022;Comeau et al, 2022;Enochs et al, 2020;Rivest et al, 2017;Schoepf et al, 2020). We are aware that this study explored only a few of the compensatory mechanisms that might be at the origin of the resilience observed for corals from Bouraké.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Understanding how calicoblastic cells regulate pH in the context of their apical and basal microenvironments within the organism has profound implications for our understanding of how and why coral calcification responds to environmental variation. It is well known that ocean acidification (decreases in seawater pH due to oceanic uptake of man-made CO 2 ) drives down pH in the ECM of many coral species (Wall et al, 2016;Comeau et al, 2019;Venn et al, 2019;Comeau et al, 2022), but a clear physiological understanding of how and why pH ECM and intracellular pH (pH i ) of the calicoblastic epithelium responds to ocean acidification is lacking. Other changes in seawater carbonate chemistry also modulate pH ECM including variation in seawater dissolved inorganic carbon concentration [DIC] (Comeau et al, 2017;McCulloch et al, 2017) but the links between seawater carbonate chemistry and pH ECM are not fully understood.…”
Section: Introductionmentioning
confidence: 99%